Réponses

2014-02-02T10:48:39+01:00
Bonjour

On sait que h(x) = ax + b

h(0) = -1 ===> a*0 + b = -1
             ===> b = -1

D'où h(x) = ax - 1

h(2) = 5 ===> a*2 - 1 = 5
            ===> 2a - 1 = 5
            ===> 2a  = 5 + 1
            ===> 2a = 6
            ===> a = 3

Par conséquent : h(x) = 3x - 1
2014-02-02T10:58:38+01:00
H (2) = 5   
a x 2 + b = 5
a2 + b = 5
b = 5 - 2a

h (0) = 1   
a x 0 + b = 1
a0 + b = 1    
b = 1 - 0a               


5 - 2a = 1 - 0a
5 - 5 - 2a = 1 - 0a - 5
2a = - 4 - 0a
2a = - 4 
a : 2 =  - 4 : 2
a = - 2
    
b = 5 - 2 x (- 2)
   = 5 - (- 4)
   = 5 + 4
   = 9